The Effectiveness Of Abdominal Streching Exercise On Mental Pain In Adolescent Women In Pekanbaru - Amalia Dwi Oktami; Hastuti Marlina; Yessi Harnani (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Abdominal muscle stretching exercises One of the efforts to suppress menstru al pain is to do abdominal stretching exercises. This exercise is useful for stretching the abdominal and pelvic muscles so that the muscles around the abdomen relax and shrink. The purpose of this study was to determine The Effectiveness Of Abdominal Muscle Stretching Exercises Against Menstrual Pain Adolescent Girls In Pekanbaru. This study used a quasi-experimental design. This study uses a minimum sample with an infinite population of young women aged 13-15 years and uses a snowball sampling technique. First day of menstrual pain in the abdomen before doing abdominal stretching exercises (43.3%) a little pain and after being given therapy (43.3% ) no pain. Whereas on low back pain before being given therapy (50%) a little sick and after being given therapy (50%) no pain. The second day of menstrual pain in the abdomen before being given therapy (43.3%) and after (50%) no pain and low back pain before (46.7%) somewhat disturbing and after therapy (50%) no pain. The results of the calculation of the Wilks lambda multivariate test with a significance value of 0.0001 < 0.05 so that there is an average change before and after abdominal stretching